The stress and free radical towards disease and aging. - May, Khin Soe (IIUM Press, 2011)
All living things will grow old, and inevitably all will die one day. This is a normal process to grow old, to have disease and die. Death is no exception. However, the rate of disease occurrence varies with different people. Moreover, the psychological distress influences the onset of age related disease and biological aging. Actually, aging is a multi-factorial process, and many contributing mechanisms have not clearly been identified yet. However, there are so many theories have been explained the underlying biological basis of aging process (Curtler, 1994). The various interactive factors which contribute to the aging process have been shown in figure